Pengujian Bakteri Coliform dan Escherichia Coli Pada Beberapa Depot Air Minum Isi Ulang di Kecamatan Palu Timur Kota Palu - Muhammad Alwi; Sri Maulina (Biocelebes, 2012)
This study was aimed to know the quality of water refills in the district of east Palu, Central Sulawesi during periode of March until May 2012, with Purposive Random Sampling Method. Ten of fortyeight water refill was chosen as the sampling. This study was quantitatively with MPN (Most Probable Number) method for determination of Coliform used Lactosa Broth (LB) medium. In addition, was also conducted a qualitative test by testing of Escherichia coli used selective medium, there are Eosine Methylene Blue Agar (EMBA) and Mac Conkey Agar and then used Gram staining. The result showed tha the water refills in the district of east Palu were not for the requirements of SNI water with bacteriological test by 1 sampling (values of MPN Coliform about 4,3x101 (43 cell/ml)), and the requirements of SNI water are 9 sampling (values of MPN coliform about 3,0x100 (<3 cell/ml)) from all the sampling. But, for the testing of Escherichia coli is negative. Key words: Coliform, Escherichia coli, Drinking-Water refill station (DAMIU)